Networks for the promotion of territorial development in the horticultural belt platense. Reflections and contributions - Seibane, Cecilia Seibane; Larrañaga, Gustavo; Kebat, Claudia; Hang, Guillermo; Ferraris, Guillermina; Bravo, María Laura (Centro de Historia Argentina y Americana, 2014)
Platense horticultural belt in a set of institutions and organizations in the public and private sector establish links between them and the productive sector with different purposes, forming networks. The work aims to understand and analyze networks partner techniques that contribute to territorial development. We used a methodology of qualitative type, conducting semi-structured interviews to public and private sector engineers and representatives of the productive sector. The results show a diversity of networks partner techniques, in which various actors participate, and promoting a set of innovations of different types.